Deficiency of monoclonal non‐specific suppressor factor beta (MNSFB) promotes pregnancy loss in mice. Issue 6 (1st June 2015) - Gu, Yan; He, Yaping; Zhang, Xuan; Shi, Yan; Yang, Qian; Yu, Lin; Sun, Zhaogui; Zhang, Huiqing; Wang, Jianmei; Gao, Xiang; Wang, Jian
SUMMARY Maternal immune tolerance to the semi‐allogenic fetus is required for successful pregnancy in mammals. Monoclonal nonspecific suppressor factor beta (MNSFB) is an immunosuppressive factor present in uterine epithelial and stromal cells, as well as in macrophages and T cells. Although the functional neutralization of MNSFB using specific antibodies against it lead to failed embryo implantation in mice, the exact role of MNSFB at the fetal–maternal interface remains unclear. The present study generated conditional heterozygous Mnsfb‐deficient (Mnsfb+/−) mice using the LoxP/Cre system. Western‐blot analyses showed that uterine MNSFB protein in Mnsfb+/− mice was remarkably down‐regulated compared to that in the wild‐type (Mnsfb+/+) mice. The litter size of female Mnsfb+/− mice was significantly reduced, which corresponded to developmental failure of embryos beyond Day 11 of pregnancy. The expression level of MNSFB protein was also lower in the failing compared to the normal embryos. An aberrant interaction between the embryos of Day‐4 pregnant wild‐type mice and endometrial stromal cells of female Mnsfb+/− mice was observed in vitro. The uterine Day‐5 abundance of P53, BAX, and BCL‐G in pregnant Mnsfb+/− mice was significantly decreased compared to that of wild‐type mice, whereas the expression of P27 and tumor necrosis factor alpha (TNFA) was elevated. By comparison, the levels of MNSFB and BAX proteins in human decidual tissues obtained from recurrent spontaneous miscarriage patients were significantly reduced compared to those obtained from legal medial abortion, highlighting the involvement of MNSFB in the pathogenesis of recurrent spontaneous miscarriage. Together, these results demonstrated that a deficiency in MNSFb is associated with pregnancy loss, probably through reduced P53 and/or increased TNFA production at the fetal–maternal interface. Mol. Reprod. Dev. 82: 475–488, 2015. © 2015 Wiley Periodicals, Inc.